Morphological and histomorphometric evaluation of autogenous bone graft resorption in rabbits treated with alendronate sodium - Teo Mario da ROSA; Alexandre da Silveira GERZSON; Diogo Souza Ferreira Rubim de ASSIS; Cláudia Cristina BIGUETTI; Mariza Akemi MATSUMOTO; Eduardo Sanches GONÇALES
Abstract Introduction Different rates of resorption are mediated by osteoclasts that may be affected by bisphosphonates during bone graft repair. Bisphosphonates are drugs that act as inhibitors of bone resorption. Objective The aim of the present study was to evaluate the rate of resorption of skullcap grafts in rabbits with and without the use of alendronate sodium. Material and method Thirty two New Zealand rabbits were divided into two groups (control group and alendronate group) and divided again into four periods (7, 14, 30 and 60 days). The control group did not receive alendronate, while animals of the experimental group received 4 mg of alendronate sodium weekly after the surgery. An 8 mm diameter bone block was removed from the parietal bone and fixed by screws to the contralateral parietal bone. During the periods of 7, 14, 30 and 60 days, the animals had undergone euthanasia and samples were removed for further analysis. Morphological and histomorphometric tests were used to compare graft thicknesses and to evaluate the newly formed bone at the interface between the graft and receptor site. The Wilcoxon and Mann-Whitney tests were used for statistical analyses. Result All grafts healed and integrated uneventfully and no statistically significant differences in resorption rates or bone deposition were detected after the final incorporation of the graft in both groups. Conclusion Alendronate Sodium did not decrease the bone graft resorption rates, but there was a tendency for better results in the control group regarding the resorption and neoformation in autogenous calvarial bone grafts in rabbits.